2022
DOI: 10.3390/pathogens11010079
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Deltacoronaviruses: Origin, Evolution, Cross-Species Transmission and Zoonotic Potential

Abstract: Porcine deltacoronavirus (PDCoV) is an emerging enteropathogenic coronavirus of swine that causes acute diarrhoea, vomiting, dehydration and mortality in seronegative neonatal piglets. PDCoV was first reported in Hong Kong in 2012 and its etiological features were first characterized in the United States in 2014. Currently, PDCoV is a concern due to its broad host range, including humans. Chickens, turkey poults, and gnotobiotic calves can be experimentally infected by PDCoV. Therefore, as discussed in this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 114 publications
(120 reference statements)
0
37
0
1
Order By: Relevance
“…Empirical evidence shows that PDCoV has cross-species transmission ability, zoonotic potential, and a wide host range. It is uncertain whether there exist other unidentified PDCoV hosts or whether the virus will infect new hosts in the future [ 8 , 13 ]. To date, no effective therapeutic agent or commercial vaccine is available for the treatment or prevention of PDCoV infection [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Empirical evidence shows that PDCoV has cross-species transmission ability, zoonotic potential, and a wide host range. It is uncertain whether there exist other unidentified PDCoV hosts or whether the virus will infect new hosts in the future [ 8 , 13 ]. To date, no effective therapeutic agent or commercial vaccine is available for the treatment or prevention of PDCoV infection [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent challenge experiments confirmed that PDCoV is an important causative agent of diarrhoea in pigs and particularly in neonates [ 6 , 7 ]. Outbreaks of pig diarrhoea caused by PDCoV were then reported in Canada, Korea, China, Japan, Vietnam, Thailand, Laos, Mexico, and Haiti [ 1 , 8 , 9 ] and caused considerable economic losses to the global pig industry [ 2 ]. Birds, chickens, turkey poults, and calves could also become PDCoV hosts under natural and experimental conditions [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Deltacoronavirus/δ-CoV (Daha yakın zamanda tanımlanan cins) içerisinde de domuzlardan (Porcine Deltacoronavirus/PDCoV) ve yabani kuşların yanı sıra, Asya leopar kedisinden izole edilen çeşitli virüsler yer almaktadır [10,11]. Lednicky olacak zoonoz bir özellik kazanma potansiyeli olduklarını vurgulamışlardır [11,12].…”
Section: Betacoronavirus Grup D (Nobecovirus Alt Cinsi) Yalnızca Yara...unclassified